The Structure and Determinants of Local Public Investment Expenditures - Hansen, Niles M. (The Review of Economics and Statistics, 1965)
DISCUSSIONS of municipal financial difficulties nearly always involve fundamental problems of local public investment requirements. It is curious, therefore, that studies of the determinants of such outlays have been so scant. One probable reason in the United States is that the relative financial responsibility for local investment of municipal, county, state, and federal governments may vary considerably from region to region and even among communities within any given region. This complexity of government structure, combined with a diversity of local accounting procedures, has probably hampered collection of adequate data. In general, studies of municipal expenditures have tended to combine current and capital outlays into a single variable.' As Brazer has pointed out, this procedure obscures much that should be revealed, since the forces which influence investment outlays are different from those affecting current expenditures.2 The present study develops a substantial number of hypotheses, covering four principal groups of causal factors affecting community investment. These center on demographic, housing, commercial, and industrial characteristics, the influences of which are then examined in the light of empirical evidence from East Flanders, a Belgian province which serves as an excellent laboratory for these purposes. Belgium is one of the world's most densely populated and highly industrialized nations. Although its total area is relatively small, the number of municipalities per unit area is very high. East Flanders, for example, covers 1150 square miles and contains 297 municipalities. This phenomenon results in part from the fact that Belgium has no equivalent to the American county; any given location is always within some municipality. All municipalities in Belgium participate in a common system of investment finance, making it possible to obtain highly standardized data for local investment. Consequently, variation in such outlays in Belgium is a more accurate reflection of differences in actual requirements than would be the case in the United States, where differential ability to pay muddies the analytic waters.3 A further element of homogeneity in the present case is the dominance of the clothing and textile sectors in all industrial municipalities. This has permitted fairly straightforward identification of industrial importance on the basis of employment data, without the complications that could arise from qualitative differences in industrial structure. The empirical evidence considered below consists of data obtained in a special municipal investment survey prepared by the author and completed by competent local authorities over a six-month period. The data include all investments in responding municipalities during the five-year period 1956-1960. The 269 respondents account for over 95 per cent of the population of the province.